2018
DOI: 10.1016/j.scitotenv.2017.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter in podzol horizons of the Amazon region: Humification, recalcitrance, and dating

Abstract: Characteristics of soil organic matter (SOM) are important, especially in the Amazon region, which represents one of the world's most relevant carbon reservoirs. In this work, the concentrations of carbon and differences in its composition (humification indexes) were evaluated and compared for several horizons (0 to 390cm) of three typical Amazonian podzol profiles. Fluorescence spectroscopy was used to investigate the humic acid (HA) fractions of SOM isolated from the different samples. Simple and labile carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
4
35
0
4
Order By: Relevance
“…In previous work by Tadini et al [13], involving the dating of these Amazonian Spodosols and determination of the humification indices, it was observed that soil P1 presented an accumulation of young organic material with a low degree of humification, which was displaced with depth, due to physical and chemical processes. The highest values for humification of the whole soil and for the humic acid fraction were obtained for the Bh-C horizon, at 240 cm.…”
Section: Samples Carbon (%) Concentration Of Metals (G/kg) Metals Arementioning
confidence: 96%
See 2 more Smart Citations
“…In previous work by Tadini et al [13], involving the dating of these Amazonian Spodosols and determination of the humification indices, it was observed that soil P1 presented an accumulation of young organic material with a low degree of humification, which was displaced with depth, due to physical and chemical processes. The highest values for humification of the whole soil and for the humic acid fraction were obtained for the Bh-C horizon, at 240 cm.…”
Section: Samples Carbon (%) Concentration Of Metals (G/kg) Metals Arementioning
confidence: 96%
“…Sample P4 was from a well-drained podzol under rainforest vegetation, with no influence of groundwater. Further details of the study area can be found in Tadini et al [13].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, the organic matter wraps the clay particles and hinders the reaction between the solidification agents and the clay particles. On the other hand, since the organic matter is acidic [17][18][19], it will produce neutralization reaction with alkaline substances produced by solidification agent hydration reaction, which will reduce the pH of the solution, and then hinders the hydration reaction of solidification agents [20][21][22]. So for S/S sludge with high total organic content (TOC), the solidification effect is often poor.…”
Section: Introductionmentioning
confidence: 99%
“…Bahan organik tanah dalam pengelolaan lahan berkelanjutan berperan dalam pengaturan dinamika unsur hara tanah (Tadini et al, 2018). Bahan organik di samping berpengaruh terhadap pasokan hara tanah juga tidak kalah pentingnya terhadap sifat fisik, biologi dan kimia tanah lainnya (Suminarti & Susanto, 2015).…”
unclassified